Elastic analysis of Shrink-fitted Thick FGM Cylinders Based on Linear Plane Elasticity Theory - Mohammad Reza Salehi Kolahi; Mohammadreza Karamooz; Hossein Rahmani (Mechanics of Advanced Composite Structures, 2020)
Nowadays, functionally graded materials (FGM) are widely used in many industrial, aerospace and military fields. On the other hand, the interest in the use of shrink-fitted assemblies is increasing for designing composite tubes, high-pressure vessels, rectors and tanks. Although extensive researches exist on thick-walled cylindrical shells, not many researches have been done on shrink-fitted thick FGM cylinders. In this paper, an analytical formulation for shrink-fitted of axisymmetric thick-walled FGM cylinders based on the linear plane elasticity theory is presented. The stresses and displacement fields in thick cylindrical shells are calculated using the real, Repeated and complex roots of characteristic equation. The displacements and stresses resulted are depicted for a case study. The results show that the material composition variation had evident effects on shrink-fit pressure in the intersection area of two fitted tubes. The value of this pressure affects radial and hoop stress distribution in FG circular cylinders walls.